2014
DOI: 10.1016/j.micres.2013.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Streptomyces strains isolated from herbal vermicompost for their plant growth-promotion traits in rice

Abstract: Six actinomycetes, CAI-13, CAI-85, CAI-93, CAI-140, CAI-155 and KAI-180, isolated from six different herbal vermi-composts were characterized for in vitro plant growth-promoting (PGP) properties and further evaluated in the field for PGP activity in rice. Of the six actinomycetes, CAI-13, CAI-85, CAI-93, CAI-140 and CAI-155 produced siderophores; CAI-13, CAI-93, CAI-155 and KAI-180 produced chitinase; CAI-13, CAI-140, CAI-155 and KAI-180 produced lipase; CAI-13, CAI-93, CAI-155 and KAI-180 produced protease; a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(108 citation statements)
references
References 38 publications
6
98
0
4
Order By: Relevance
“…The reason for selecting only β-1,3-glucanase, IAA and siderophore traits for expression profiles is that these three traits are directly linked to growth promotion of the plants. Similar results were also reported by Gopalakrishnan et al (2013bGopalakrishnan et al ( , 2015a which support the PGP by Streptomyces strains.…”
Section: Discussionsupporting
confidence: 90%
“…The reason for selecting only β-1,3-glucanase, IAA and siderophore traits for expression profiles is that these three traits are directly linked to growth promotion of the plants. Similar results were also reported by Gopalakrishnan et al (2013bGopalakrishnan et al ( , 2015a which support the PGP by Streptomyces strains.…”
Section: Discussionsupporting
confidence: 90%
“…Lastly, research to develop methods of bioinoculant delivery and timing must be carried out in the greenhouse and field to maximize the plant response to the applied bioinoculant. It has been found that applying streptomycetes is different to applying Gram-negative bacteria because better plant responses have generally been obtained when the streptomycete application to the soil or substrate occurred before sowing the seeds, thus allowing the selected strain to colonize and establish [6,137,138].…”
Section: Biotechnological Application Of Pgps In Agriculturementioning
confidence: 99%
“…Streptomyces spp. have been widely reported and demonstrated under field conditions as plant growth-promoters and biocontrol agents in both cereals and legumes (Tokala et al, 2002;Nassar et al, 2003;Sadeghi et al, 2012;Gopalakrishnan et al, 2013Gopalakrishnan et al, , 2014Gopalakrishnan et al, , 2015Gopalakrishnan et al, , 2016a. In the present investigation, when the Streptomyces spp.…”
Section: Discussionmentioning
confidence: 99%
“…They play an important role, not only on plant growth-promotion (PGP), antagonistic action against pathogens and insect pests and biofortification traits in many agriculturally important crops, but also on decomposition of organic materials and production of secondary metabolites (Glick, 2010). Plant growthpromoting properties of actinomycetes was reported on cereals (such as wheat (Sadeghi et al, 2012), rice (Gopalakrishnan et al, 2014) and sorghum (Gopalakrishnan et al, 2013)) as well as legumes (such as bean (Nassar et al, 2003), chickpea (Gopalakrishnan et al, 2015, pigeonpea and pea (Tokala et al, 2002). Actinomycetes have also been demonstrated for biocontrol of soil-borne pathogens (Mahadevan and Crawford, 1997;TrejoEstrada et al, 1998;Macagnan et al, 2008;Gopalakrishnan et al, 2011) and insect pests (Gopalakrishnan et al, 2016c;Sathya et al, 2016 a, b).…”
Section: Introductionmentioning
confidence: 99%